How to be Modern: The Darantière Press and Anglo-American Writers in France - Fiona McMahon (Transatlantica)
The collaboration between Sylvia Beach, James Joyce, and the Dijon printer Maurice Darantière that resulted in the first printing of Ulysses in 1922 was commemorated in a 1988 study by the modernist scholar Jean-Michel Rabaté: Maurice Darantière, les années vingt: bibliographie d’imprimeur. The bibliography appended to the investigation of Darantière's publishing history (1900-1928) reveals a remarkable number of volumes of English-language poetry, essays and fiction during this period. Along with French translations of a range of English-language short stories (by Sherwood Anderson or Edgar Allan Poe), Darantière’s catalogue boasts over a dozen English-language volumes, including those by some of the key figures of anglophone literary modernism (Bryher, Robert McAlmon, Gertrude Stein, William Carlos Williams, H.D.). Darantière’s willingness to print books in a language other than French is a tribute not only to the audaciousness of his enterprise but to the network of influence established among Anglo-American writers, publishers and booksellers in France in the first decades of the twentieth century. What can a new examination of the Darantière collection (Bibliothèque municipale, Dijon) bring to light about the mediation of avant-garde Anglo-American writing in France and what Lawrence Rainey has called the “commodification” (44) of modernist print culture? The contribution of Darantière in the dissemination of Anglo-American literary experiment will be measured alongside the expanding role of the printer, from craftsman to vector of the new expatriate writing.